Magnetism and Accelerator-Based Light Sources Proceedings of the 7th International School ''Synchrotron Radiation and Magnetism'', Mittelwihr (France), 2018 - Bulou, Hervé; Joly, Loïc; Mariot, Jean-Michel; Scheurer, Fabrice (Springer Proceedings in Physics, 2021)
This open access book collects the contributions of the seventh school on Magnetism and Synchrotron Radiation held in Mittelwihr, France, from 7 to 12 October 2018. It starts with an introduction to the physics of modern X-ray sources followed by a general overview of magnetism. Next, light / matter interaction in the X-ray range is covered with emphasis on different types of angular dependence of X-ray absorption spectroscopy and scattering. In the end, two domains where synchrotron radiation-based techniques led to new insights in condensed matter physics, namely spintronics and superconductivity, are discussed. The book is intended for advanced students and researchers to get acquaintance with the basic knowledge of X-ray light sources and to step into synchrotron-based techniques for magnetic studies in condensed matter physics or chemistry.